2005
DOI: 10.1002/lt.20510
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenation during hypothermic rat liver preservation: An in vitro slice study to demonstrate beneficial or toxic oxygenation effects

Abstract: Hypothermic machine perfusion (HMP) of abdominal organs is shown to be superior compared to cold storage. However, the question remains if oxygenation is required during preservation as oxygen is essential for energy resynthesis but also generates toxic reactive oxygen species (ROS). To determine if oxygenation should be used during HMP, urea-synthesis rate, adenosine triphosphate (ATP), and generation of ROS were studied in an in vitro model, modeling ischemia-reperfusion injury. Furthermore, expression of un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 49 publications
6
38
0
Order By: Relevance
“…After 8 h reservoir saturation was reached and oxygen uptake by the liver remained constant but still considerable (35 kPa). This finding is in accordance with other authors, 9,10,13 who showed an improved liver viability after oxygenated versus nonoxygenated HMP indicating that the liver, even under hypothermic conditions, has a considerable oxygen demand.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…After 8 h reservoir saturation was reached and oxygen uptake by the liver remained constant but still considerable (35 kPa). This finding is in accordance with other authors, 9,10,13 who showed an improved liver viability after oxygenated versus nonoxygenated HMP indicating that the liver, even under hypothermic conditions, has a considerable oxygen demand.…”
Section: Discussionsupporting
confidence: 94%
“…Previously, many authors have pointed at the potential importance of additional oxygenation during liver HMP. 9,10,13,25,31 Based on the data of Fuija et al 10 as well as our experiments 13 the required partial oxygen pressure was determined at 55 kPa 31 to comply with total liver oxygen demand during HMP. In addition to an adequate perfusion, we concluded that the hypothermic liver uses oxygen and thus oxygenation of the perfusate, even at low temperatures, remains necessary.…”
Section: Introductionmentioning
confidence: 99%
“…To further improve organ viability, a more dynamic preservation method is needed to better fulfil the metabolic demands of damaged organs. Therefore, many groups have recently switched gears and are revisiting the possibilities of hypothermic machine perfusion (HMP) (103)(104)(105).…”
Section: New Solutionsmentioning
confidence: 99%
“…Several studies demonstrated that perfusion with oxygenated solutions prevented ATP loss and avoided the injurious ischemic cascades that are set into motion after ATP depletion [7,8,9,10]. The role of oxygenation has also been supported by other studies [11,12,13,14]. More recently, Figure. 1: Prototype liver device during HMP.…”
Section: Introductionmentioning
confidence: 90%